Monoclonal antibodies - Spears, David (Oxford : Science Pictures for Oxford University Press, 1994)
The video describes the practical uses to which conventional polyclonal antisera have been put, but also points out their limitations. It explains the principles of methods used to generate and select the hybridoma cell linesproducing monoclonal antibodies of desired specificities from the huge range of immunoglobulins potentially available in an individual's B lymphocyte repertoire.
Title from data sheet.
Keywords: Monoclonal antibodies